Conceptualizing Nostalgic Echo Chambers - Dam, Christian ; 0000-0003-3517-0571; Hartmann, Benjamin; Brunk, Katja H. (Association for Consumer Research, United States, 2025-10-09 - 2025-10-11, 2025)
While nostalgia has been a prominent theme in consumer research, little research explicitly addresses its dark side. This conceptual paper unpacks nostalgic echo chambers and their three axiological features of polarization, singularization, and ideologization to inform future consumer research on the implications of nostalgic echo chambers for consumers and society.